Money and the Nominal Interest Rate in an Inflationary Economy: An Empirical Test - Blejer, Mario I. (Journal of Political Economy, 1978)
Changes in the money supply are expected to affect the nominal rate of interest in opposite directions: the liquidity and credit effects tend to depress the rate, while higher inflationary expectations work in the opposite direction. Theoretical studies suggest that, although liquidity and credit effects initially dominate, they are eventually more than offset by the expectations effect. These results are confirmed in countries of mild inflation. The results obtained here for a highly inflationary country–Argentina–indicate that the expectations effect is dominant and that any change in the rate of monetary disequilibrium was fully transmitted to the nominal interest rate.